Trend in milk production in Himachal Pradesh - CHAUHAN, S K (The Indian Journal of Animal Sciences, 2013)
Species-wise milk production data were collected for Himachal Pradesh, mainly to examine the growth pattern and its projections for demand and supply. The data pertained to 1977Â·7'& to 1989Â·90. Over a period of 13 years, the cow and buffalo milk production increased by 163.70 and 52.29% respectivcly. Goat milk production decreased and fluctuated, Buffalo maintained hs first position by contributing 52,69%to the total milk production, The per caput daily milk availability was 288 g higherthan the national average of 174 g. Buffalo and cow milk production increased significantly @ 4,16 and 8,35% respectively. Consequently, the total milk production in the state increased significantly at the compound growth rate of 5,68% per annum. The average milk yield of cow was lower lhan of buffalo, but increased at a faster ratethan of buffalo mainly due to the introduction of superior breeds, The compound growth rate of 5.63 and 1.96% in the milk yield of cow and buffalo was higher than the national average of 7,29 and 3,720% as well as the world average of 1.02 and 3,93% per annum respectively, The milk supply being on the higher side (969.13 thousand tonnes) than its nutritional requirement of 587,24 thousand tonnes by the year 2000, calls for a careful planning for its optimum utilization